2019
DOI: 10.3389/fncel.2019.00252
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Tet Is Expressed in Midline Glia and Is Required for Proper Axonal Development

Abstract: Ten-Eleven Translocation (TET) proteins are important epigenetic regulators that play a key role in development and are frequently deregulated in cancer. Drosophila melanogaster has a single homologous Tet gene ( dTet ) that is highly expressed in the central nervous system during development. Here, we examined the expression pattern of dTet in the third instar larval CNS and discovered its presence in a specific set of glia cells: midline glia (MG). Moreover, dTet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 49 publications
(66 reference statements)
4
24
0
Order By: Relevance
“…1 E ). This is in line with previously published knock-down experiments of dTet reporting locomotion defects ( Wang et al, 2018 ; Ismail et al, 2019 ). Adult dTet-deficient flies cannot fly or climb and are prone to fall over while walking.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…1 E ). This is in line with previously published knock-down experiments of dTet reporting locomotion defects ( Wang et al, 2018 ; Ismail et al, 2019 ). Adult dTet-deficient flies cannot fly or climb and are prone to fall over while walking.…”
Section: Resultssupporting
confidence: 93%
“…Co-staining with the pan-neuronal marker Embryonic lethal abnormal vision (ELAV) showed that Tet[MI05009] -G4 is expressed in most neurons of the ventral nerve cord (VNC; L3) and adult central brain ( Fig. 2 B ) similar what has been published for an endogenous dTet -GFP reporter ( Ismail et al, 2019 ). Tet[MI04973]- G4 on the other side, showed less overlap with the neuronal marker ELAV ( Fig.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations